Colloidal behavior of aqueous cellulose nanocrystal suspensions. (May 2017) - Oguzlu, Hale; Danumah, Christophe; Boluk, Yaman
Abstract: In this short review, we discuss the colloidal microstructure of sulfonated cellulose nanocrystal (CNC) suspensions and connect to their rheological behavior in the presence of electrolyte, by changing its surface chemistry and also in dilute water soluble polymer solutions. Presence of electrolyte has a significant effect depending both on the concentrations of CNC and electrolyte. The salt presence on the microstructure of CNC suspensions were successfully explained by DLVO theory. Even within the dilute concentration regime (< 0.5 vol%), CNC particles can form gels either by adding high concentration of electrolyte or low concentration (around overlapping concentration) of non-adsorbing polymer. Addition of water soluble polymers may cause depletion of CNC if the polymer is not adsorbing. It is believed that the depletion flocculation is the case for the effects of carboxymethyl cellulose (CMC) polymer chains in CNC suspensions and cause significant gelling. Graphical abstract: